The Role of Customer Engagement in Islamic Banking - Maziyah Mazza Basya (Universitas Airlangga, 2018)
The marketing strategy to be engaged with customer of an Islamic bank must be concerned with its ability to gain a competitive advantage and establish a strong competitive position without neglecting an Islamic business ethic. Customer engagement (CE) in Islamic bank does not take any matter of competing on product and prices, but rather in stressing quality of the services they provide appealing customers conscience. This research attempts to enhance understanding of CE related in its role to increase the quantity and loyalty of Islamic banks customers with the Islamic business ethics point of view. This is a qualitative research that develops customer engagement concept that relevant to be applied in Islamic banking by collecting some of CE theories regarding the CE approach through relationship marketing and analyze them with Islamic business ethic overview. CE in Islamic banking has to be relied with Sharia’s law. The main point of CE in Islamic banking is not only to have a good relationship with the customer and be a brotherhood, but also to reach the Islamic banking purposes.